Disciplinary attitudes and cigarette smoking: a comparison of two schools. Issue 6356 (11th December 1982) - Porter, A
Abstract : Two British boarding schools for boys with different disciplinary policies in respect of cigarette smoking were identified. Questionnaires were sent to the young "old boys" of each school to determine their present smoking habit and most were returned (school A 81%, school B 83%). Significantly more responders smoked who had been to the less strict school (school A 39%, school B 30%, p less than 0.05). These figures probably underestimate the smoking prevalence in the two complete groups. The results suggest that measures that reduce the exposure of an uncommitted adolescent to peer group smoking decrease the chances of tobacco dependence in adulthood.